Pengaruh Intellectual Capital, Leverage, Audit Tenure dan Profitabilitas Terhadap Integritas Laporan Keuangan - Purba, Jamian; Fuadi, Agus (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Financial reports are a means for shareholders, creditors, goverments agencies and other parties to find out the condition and performance of the company.Thus the integrity of financial reports become very important in making decisions for the parties as mentioned above. The porpose of this study was to determine the effect of intellect capital, leverage, audit tenure and profitability on the integrity of the financial statements of companies listed in the food and beverage sector on the Indonesia Stock Exchange for the period 2017-2021. This study uses a quantitative method. The data source used comes from the website www.idx.co.id. The data analysis technique used is multiple linier regression analysis using SPSS 22. The results of this study indicate that intellectual capital and returned on assets have significant and positive effect. Leverave and audit tenure has no significant effect to integrity of financial statement of the companies listed in the food and beverage sector in Indonesia Stck Exchange Year 2017-2021